Interoperability in digital public services and administration : bridging e-government and e-business - Charalabidis, Yannis, 1967- (Hershey, PA : Information Science Reference, 2011)
'This book provides the latest research findings such as theoretical foundations, principles, methodologies, architectures, technical frameworks, international policy, standardization and case studies for the achievement of interoperability within the provision of digital services, from administration and businesses toward the user citizens and enterprises'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Internet in public administration; Political participation -- Technological innovations; Electronic commerce